A digital earthmoving equipment service platform to enhance customer aftermarket experience - Molele, Nnanna Reshoketswe (University of the Witwatersrand, Johannesburg, 2023)
The absorption of technology solutions has become more and more prevalent in the mining and construction industries. Mining and construction companies worldwide are implementing technology solutions as they seek to improve the safety, productivity, and profitability of their earthmoving operations. One of the most critical and capital intensive assets that these operations own and operate is their earthmoving equipment. The maintenance and repair of the equipment also contributes heavily to the operational expenditure of such operations (19% for large operations). It is critical for these operations for their equipment maintenance to be done in a timely manner, at the lowest possible cost, and with the highest possible level of quality so as to manage operational costs and reduce the impact of machine downtime on productivity. This business venture is based on a South African company that supplies earthmoving equipment to mining and construction companies in the Southern Africa market. The company not only supplies equipment, but also aftermarket solutions (parts and maintenance & repair services). In the past five financial years, the company has seen a decline in revenue from its service business where it sells technician labour to the mining and construction markets for equipment maintenance and repairs. Its customer net loyalty score is also sitting at an average of 32% in the same period. Customer loyalty has been negatively impacted by customer dissatisfaction with the organisation’s service quality, turnaround time, and communication, to name a few. The service business profitability has also been on a downward trend (14% in 2018 to 9% in 2022). Given the size of the organisation and the number of countries it operates in, this paper only focuses on the Zambia market where the company’s service business is currently seeing negative profitability trends and the lowest customer net loyalty score of 18%. In response to this business challenge, this paper focuses on using technology and third party equipment service providers (labour for maintenance and repairs) to propose a business model that will create shared stakeholder value. The business model seeks to address current customer challenges while improving the business profitability and making it more feasible for third partner service providers to partner with the organisation instead of operating as its competitors
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digitalisation; Digital Platforms; Gig Economy; Business Profitability; UCTD; SDG-8: Decent work and economic growth